ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN INVESTASI BAGI GENERASI MILINEAL (STUDI KASUS PADA MAHASISWA STIE APRIN PALEMBANG) - Senen HAR (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2024)
This study aims to analyse the factors that influence investment decisions in the millennial generation, especially STIE APRIN Palembang students. Using a case study method, this research used thematic analysis to extract in-depth information from 30 student respondents. Data was collected through questionnaires and in-depth interviews, then analysed using a thematic approach to identify key patterns and themes. The results showed that factors such as financial literacy, financial behaviour, economic conditions, and government policies strongly influence millennials' investment decisions. All respondents had a basic understanding of investment, but only 50% had attended investment training. The findings indicate the need for increased financial literacy education and training programmes among university students.